Tratti linguistici in comune nei dialetti italogreci e italiani dell'Italia meridionale con particolare riguardo all'uso dell'infinito - Szabó, Anita Noémi (Verbum – Analecta Neolatina, 2011)
In the southern part of Italy, especially in Calabria, Salento and Sicily, there was an important presence of Greek colonies throughout history and as a result of this close geographical relation, there are several linguistic features shared by these languages. The main subject of this paper is the evolution of the infinitive in Italian and Greek as well as the influence of the disappearance of the Greek infinitive on the Southern Italian dialects.